Influence of chain length of long-chain fatty acid surfactant on the thermal conductivity of magnetite nanofluids in a magnetic field - Dadwal, Arun; Dadwal, Arun (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2018)
Stable magnetic nanofluids are prepared by dispersing long-chain fatty acid surfactants coated magnetite (Fe3O4) nanoparticles in toluene and investigated the effect of chain length of the surfactant molecules on the thermal conductivity of the magnetite nanofluids in a magnetic field. Superparamagnetic magnetite nanoparticles having a comparable particle size (similar to 10 nm) are coated with three different long-chain fatty acid surfactants; myristic acid (C13H27COOH), palmitic acid (C15H31COOH) and stearic acid (C17H35COOH). The thermal conductivity of the nanofluids, in a magnetic field, is found to decrease with increasing the chain length of the surfactant molecule. Among the three fluids, the shorter chain myristic acid coated nanofluid showed larger enhancement in the thermal conductivity at smaller fields as compared to the other fluids. The results indicated that the chain length of the surfactant molecule present on the surface of the magnetite nanoparticles affect the thermal conductivity of the magnetic nanofluid in an external magnetic field, due to the difference in the extent of interdigitation of the surfactant molecules.

Metamagnetism in nanosheets of Co-II-MOF with T-N at 26 K and a giant hysteretic effect at 5 K - Gupta, Kriti; Dadwal, Arun; Rana, Shammi; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2018)
Herein, we have synthesized at room-temperature two-dimensional nanosheets of a MOF comprised of cobalt(II) ion with benzenedicarboxylic acid ligand, which exhibited unusual magnetic properties. Direct-current magnetic susceptibility revealed an anti-ferromagnetic (AFM) transition at 26 K (Neel temperature, T-N) followed by a canting of the spin moments along with the concomitant appearance of a sigmoidal-shaped magnetization versus field (M-H) curve at 15 K. Such a canted AFM ordering led to nonzero remnant magnetization with a remarkably high coercive field of similar to 10 kOe at 5 K. Metamagnetism was further: substantiated by the alternating-current magnetic susceptibility measurements.

Embedding S=1/2 Kagome-like lattice in reduced graphene oxide - Gupta, Kriti; Jha, Plawan Kumar; Dadwal, Arun; Debnath, Anil K.; Jaiswal, Ishan; Rana, Shammi; Joy, Pattayil A.; Ballav, Nirmalya (Journal of Physical Chemistry Letters, 2019)
An elegant platform to explore frustrated magnetism is the kagome spin lattice. In this work, clinoatacamite, a naturally occurring S = 1/2 kagome-like antiferromagnetic insulator, is synthesized in water at ambient pressure for the first time from a cuprous chloride (CuCl) precursor whereby Cu(I) was spontaneously oxidized to Cu(II) in the form of clinoatacamite [Cu-2(OH)(3)Cl] with a simultaneous reduction of graphene oxide (GO) to reduced graphene oxide (rGO) in one pot. A stable nanocomposite of phase-pure clinoatacamite nanocrystals embedded in the rGO matrix was isolated. The clinoatacamite-rGO nanocomposite was determined to be magnetically active with a markedly enhanced coercive field of similar to 2500 Oe at S K as well as electronically active with a conductivity value of similar to 200 S.m(-1) at 300 K. Our results illustrate an avenue of combining exotic magnetic and electronic lattices without impeding their individual characteristics and synergistically generating a new class of magnetic semiconductors.

Size-controlled cobalt ferrite nanocrystals: magnetically separable reusable nanocatalysts for selective oxidation of styrene - Jeyavani, Vijayakrishnan; Pawar, Sayali; Dadwal, Arun; Joy, Pattayil Alias; Mukherjee, Shatabdi Porel (ChemistrySelect, 2019)
Superparamagnetic cobalt ferrite (CFO) nanocrystals (NCs) with sizes similar to 6 nm and similar to 4 nm were synthesized using a facile solvothermal method using fatty acids, lauric acid and stearic acid, as the capping agents. The synthesized nanocrystals were well characterized by XRD, FT-IR, XPS, SEM and TEM. The formation mechanism was explored and it was shown that the fatty acid was actually chemisorbed as a carboxylate onto the surface of CFO NCs. The experimental results specify that the size and size distribution of the CFO NCs were highly dependent on the length of fatty acid hydrophobic chain. Corresponding changes of the magnetic properties were investigated by measuring magnetization as a function of field and temperature, which suggest that the CFO NCs were superparamagnetic in nature. The catalytic properties for the oxidation of styrene in organic medium were examined by using the synthesized CFO NCs with sizes similar to 6 nm and similar to 4 nm. The synthesized CFO NCs, well dispersible in organic media, were demonstrated to be highly catalytically active, reached 100% conversion of styrene in 12 h with similar to 77% and similar to 82% selectivity for styrene oxide respectively. The magnetic CFO nanocatalysts were easily separated and recovered from the reaction medium by an external magnet, and reused for several cycles without losing catalytic selectivity for styrene oxide.
Keywords: Cobalt ferrite; epoxidation; Fatty acids; magnetic properties; nanocrystals

Exploring magnetic XY behavior in a quasi-2D anisotropic triangular lattice of Cu(II) by functionalized graphene - Gupta, Kriti; Dadwal, Arun; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2020)
Study on magnetism in two-dimensional (2D) spin-lattices is advancing rapidly. In this work, phase-pure botallackite (Bo) (Cu-2(OH)(3)Br), a quasi-2D S = 1/2 anisotropic triangular spin-lattice is stabilized over 2D reduced graphene oxide (rGO) nanosheets via simple oxidation-reduction reaction chemistry. In comparison to polycrystalline Bo, such an anchoring resulted in the oriented growth of Bo crystallites in the Bo-rGO system. The Bo-rGO nanocomposite was found to be magnetically active with a Neel transition at 8.9 K, crossing over to possible XY anisotropy at similar to 5 K-as revealed by complementary dc and ac susceptibility measurements-an unprecedented observation in the field assigned to an interfacial effect. This work demonstrates the potential usage of nonmagnetic 2D functionalized graphene to significantly modulate the magnetic properties of 2D spin-lattices.

Integrating structurally perfect s=1/2 kagome-lattice with reduced graphene oxide - Gupta, Kriti; Dadwal, Arun; Ninawe, Pranay; Joy, Pattayil A.; Ballav, Nirmalya (Journal of Physical Chemistry C, 2020)
S = 1/2 kagome-lattice hydroxychlorides are promising candidates for realizing the elusive quantum spin liquid (QSL) state. Herbertsmithite [Cu3Zn(OH)(6)Cl-2], a naturally occurring hydroxychloride mineral from the class of atacamites {[Cu-4-xMx(OH)(6)X-2] where M = Zn, Cu, Co, Ni and X = Cl, Br, I}, is one of the most appealing systems to study the QSL state because of the presence of a structurally perfect S = 1/2 kagome-lattice. It is an electrical insulator. However, realizing phase-pure herbertsmithite without imposing harsh reaction conditions remained synthetically challenging. In this work, for the first time, we have synthesized phase-pure herbertsmithite as well as its structural analogue paratacamite, [ZnxCu4-x(OH)(6)Cl-2; 0.33 = x < 1], at ambient reaction conditions. Furthermore, taking graphene oxide (GO) as an additional precursor in the reaction mixture, we have successfully integrated phase-pure crystallites of herbertsmithite (H) and paratacamite (P) with nanosheets of semiconducting and diamagnetic reduced graphene oxide (rGO) by in situ oxidation-reduction reaction. The isolated H-rGO and P-rGO systems were found to be magnetic semiconductors inheriting strong spin frustration from H and P, and semiconductivity from rGO. The H-rGO system in particular exhibited negative Seebeck coefficient (n-type semiconductor) with a thermoelectric power factor of 0.1 mu W center dot m(-1)center dot K-2 at 400 K. We anticipate the simple chemical principles outlined in this work to be useful for studying a variety of complex QSLs including electron doping. Also, semiconducting and rather unconventional materials of such metal oxochlorides with rGO isolated here need further exploration in view of thermoelectric applications.

Magnetism in bimetallic NiII-CoII coordination polymer - Gupta, Kriti; Dadwal, Arun; Joy, Pattayil; Ballav, Nirmalya (AIP Conference Proceedings, 2020)
Co-BDC ([Co2(OH)2BDC], H2BDC = 1,4-benzenedicarboxylic acid) is known to possess metamagnetism originating from the antiparallel spins and high magneto crystalline anisotropy of Co(II).1 Herein, we have introduced a bimetallic concept by incorporating Ni(II) along with Co(II) in the same coordination polymer to modulate the magneto crystalline anisotropy in the lattice which in turn, affects the overall magnetic response of the coordination polymer. The Curie-Weiss equation fit suggested antiparallel arrangement of the spins (θ ≈ -62.5 K) of Ni(II) and Co(II) arranged in alternate fashion. The cusp in magnetization was observed at 7 K (Tc) with a significant coercive field of ∼750 Oe at 5 K.

Particle size effect in different base fluids on the thermal conductivity of fatty acid coated magnetite nanofluids - Dadwal, Arun; Joy, P. A. (Journal of Molecular Liquids, 2020)
The effect of particle size on the thermal conductivity of nanofluids is studied by dispersing myristic acid coated magnetite (Fe3O4) nanoparticles in two different base fluids; toluene and kerosene. Magnetite nanoparticles of three different sizes 4, 7 and 10 nm dispersed in toluene and kerosene showed a linear increase in the thermal conductivity with increasing concentration of the nanopartides, above a critical concentration. The critical concentration below which the thermal conductivity remained unchanged with the concentration of the nanopartides is found to be lower for the kerosene-based fluids. The variation of thermal conductivity with particle size is without any clear trend. However, within the measurement errors (+/- 1%), the toluene-based fluids showed a decrease in the thermal conductivity with increasing particle size, whereas the opposite trend is observed for the kerosene-based fluids. Also, the kerosene-based fluids at similar concentrations of the nanopartides showed relatively larger enhancement in the thermal conductivity than the toluene-based fluids. The observed role of the base fluid in enhancing the thermal conductivity is correlated with the difference in the solvent-surfactant interactions which in turn affect the interfacial thermal resistance at the particle-fluid interface. The thermal conductivity of the nanofluids in toluene and kerosene is also found to show different trends with the size of the particles in the presence of an external magnetic field. The difference in the enhancement of thermal conductivity of the fluids in a magnetic field is explained in terms of the differences in the magnetic dipolar interactions, clustering/ agglomeration, and magnetic characteristics of the samples as well as the characteristics of the base fluid. (C) 2020 Elsevier B.V. All rights reserved.

Possible electron doping of geometrically perfect spin-1/2 kagome-lattice barlowite by reduced graphene oxide - Gupta, Kriti; Ninawe, Pranay; Jain, Anil; Dadwal, Arun; Anas, M.; Malik, V. K.; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Physical Review B, 2021)
Doping of quantum spin liquid (QSL) insulators by electron or hole leads to intriguing phase transitions to metallic and superconducting states. The barlowite family with geometrically perfect S = 1/2 kagome planes and tunable interkagome coupling is an emerging platform to realize spin-ordered, valence bond crystal, QSL states. Theoretical investigations on electron doping revealed localized states in the band gap of barlowite unlike metallicity in cuprate (Nd2CuO4). We present successful anchoring of phase-pure barlowite crystallites onto reduced graphene oxide (rGO). The resulting barlowite-rGO system was found to be an electrical semiconductor with Arrhenius activation energy of 0.07 eV. Semiconducting properties of the barlowite-rGO system were further modulated with retention of structural integrity. We have attributed such a transformation of electrical transport response to plausible electron doping thereby making charge-doping experiments on barlowite and its analogs propitious.

Blend of neem oil based polyesteramide as magnetic nanofiber mat for efficient cancer therapy - Patel, Pratikshkumar R.; Singam, Amarnath; Dadwal, Arun; Gundloori, Rathna Venkata Naga (Journal of Drug Delivery Science and Technology, 2022)
Stearic acid-coated magnetic nanoparticles (SMN) and FU (5-Fluorouracil) were immobilized in the blends of neem oil-based polyesteramide and fabricated as nanofiber mat (NM) for controlled release of FU under the influence of an external magnetic field for targeted drug delivery to treat cancer efficiently. Analyzed the surface morphology of the fibers using E-SEM, it was observed that the fibers were smooth with the diameter ranging from 250 to 450 nm. TEM studies showed the uniform distribution of SMN in the nanofibers. The physico-chemical properties of NM and raw materials were analyzed using FTIR, TGA, and XRD. The results suggested that the polymers were well blended. In-vitro FU release studies of the NMs recorded a significant difference in the cumulative percentage of FU release from SMN-NMs. The SMN-NMs released 95% of FU in 4 h, whereas, NMs released 83% of FU in 24 h. The cell viability assay for the NM was evaluated in the L929 mouse fibroblast cells, where >75% of cells were viable. The hemolysis assay for the developed SMN-NF showed <5% of hemolysis, which indicated the NMs were safe for application. The anti-cancer activity of FU loaded SMN-NF was analyzed in the MCF-7 cancer cell line, which recorded more than 50% cell death within 24 h. From SQUID analysis, we found that the 10% SMN were superparamagnetic in nature, the magnetization at 30 kOe was observed to be 4.3 emu/g. Based on the in vitro results, we concluded that the developed SMN-NMs are recommended for in vivo studies to understand their efficacy for the targeted drug delivery to treat cancer.
Keywords: 5-Fluorouracil; drug release; electrospinning; Magnetic nanoparticles; nanofibers; Stearic acid